The Constitutionality of the Recentralization of Forestry Authority in Indonesia from the Perspective of Regional Autonomy - Ilham Aji Pangestu; Tiara Ayu Lestari; Dian Yulviani (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
The Indonesian Constitution guarantees the broadest possible regional autonomy under Article 18(5) of the 1945 Constitution. However, Law No. 6 of 2023 and Government Regulation No. 23 of 2021 have recentralised forestry authority that had previously been decentralised to regional governments. This study aims to analyze the constitutional framework governing the distribution of authority between the central and regional governments in forest management and to assess the constitutionality of the recentralization introduced through both regulations. This study employs normative legal research that is prescriptive-analytical in nature, utilizing statutory and conceptual approaches and applying Hans Kelsen's Stufenbau Theory, the principles of decentralization and subsidiarity, and the doctrine of state control rights. The findings indicate that the recentralization of forestry authority lacks a valid constitutional basis. The policy substantively reclassifies forestry from a concurrent affair into an exclusive central government authority without amending the organic regional government law. It also fails the proportionality test, inherits procedural defects from Constitutional Court Decision No. 91/PUU-XVIII/2020, and undermines vertical checks and balances mechanisms. This study implies the necessity of normative reconstruction grounded in the subsidiarity principle. The four-layer proportionality test developed herein can be applied by the Constitutional Court as an evaluative framework for sectoral policies that potentially reduce regional autonomy.